Chronic heart failure with diabetes mellitus is characterized by a severe skeletal muscle pathology. Issue 2 (21st December 2019) - Garnham, Jack O.; Roberts, Lee D.; Espino‐Gonzalez, Ever; Whitehead, Anna; Swoboda, Peter P.; Koshy, Aaron; Gierula, John; Paton, Maria F.; Cubbon, Richard M.; Kearney, Mark T.; Egginton, Stuart; Bowen, T. Scott; et al.
Abstract: Background: Patients with coexistent chronic heart failure (CHF) and diabetes mellitus (DM) demonstrate greater exercise limitation and worse prognosis compared with CHF patients without DM, even when corrected for cardiac dysfunction. Understanding the origins of symptoms in this subgroup may facilitate development of targeted treatments. We therefore characterized the skeletal muscle phenotype and its relationship to exercise limitation in patients with diabetic heart failure (D‐HF). Methods: In one of the largest muscle sampling studies in a CHF population, pectoralis major biopsies were taken from age‐matched controls ( n = 25), DM ( n = 10), CHF ( n = 52), and D‐HF ( n = 28) patients. In situ mitochondrial function and reactive oxygen species, fibre morphology, capillarity, and gene expression analyses were performed and correlated to whole‐body exercise capacity. Results: Mitochondrial respiration, content, coupling efficiency, and intrinsic function were lower in D‐HF patients compared with other groups ( P < 0.05). A unique mitochondrial complex I dysfunction was present in D‐HF patients only ( P < 0.05), which strongly correlated to exercise capacity ( R 2 = 0.64; P < 0.001). Mitochondrial impairments in D‐HF corresponded to higher levels of mitochondrial reactive oxygen species ( P < 0.05) and lower gene expression of anti‐oxidative enzyme superoxide dismutase 2 ( P < 0.05) and complex I subunit NDUFS1 ( P < 0.05). D‐HF was also associated with severe fibre atrophy ( P < 0.05) and reduced local fibre capillarity ( P < 0.05). Conclusions: Patients with D‐HF develop a specific skeletal muscle pathology, characterized by mitochondrial impairments, fibre atrophy, and derangements in the capillary network that are linked to exercise intolerance. These novel preliminary data support skeletal muscle as a potential therapeutic target for treating patients with D‐HF.